StatMAP Special Interest Group (SIG) - Joseph, Corina; Pereira, Helen; Ramli, Atikah; Chiew, Fei Ha; Jack, Suriani; Abu Samah, Aizimah (Universiti Teknologi MARA, Sarawak, 2025)
Statistics is a very important discipline. Sound practical knowledge in statistics is a vital ingredient for success in many areas of university study as well as professional careers. However the learning and teaching of statistics can be quite exacting. Many students and even some lecturers face difficulties especially in the areas of hypothesis testing, sampling distribution, estimation, forecasting, multivariate analysis and quality control.